Utility of microRNAs in Exhaled Breath Condensate as Diagnostic Biomarkers to Differentiate Pulmonary Sarcoidosis from Pulmonary Tuberculosis - Rai, Divyanjali; PP, Adwika; Tak, Jaya; Bangaru, Sunil; Pattnaik, Bijay; Yadav, Sunita; Kumari, Seetu; Kumari, Jyoti; verma, Umashankar; Yadav, Geetika; Dhaliwal, RS; Bhatraju, Naveen; et al. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background and aim: Pulmonary sarcoidosis and pulmonary tuberculosis (PTB) are two granulomatous diseases with similar clinical presentations. This study explored the potential of microRNAs (miRNAs) in exhaled breath condensate (EBC) as non-invasive diagnostic biomarkers to distinguish between pulmonary sarcoidosis and PTB. Methods: EBC samples were collected from 46 participants (20 with PTB, 26 with pulmonary sarcoidosis) and 20 healthy controls and miRNA profiling was done. Differentially expressed miRNAs were further validated using qRT-PCR in independent cohorts in EBC (17 PTB, 18 sarcoidosis, and 25 controls) and blood (10 PTB, 10 sarcoidosis, and 10 controls). Results: Initial profiling identified 19 miRNAs differentially expressed between pulmonary sarcoidosis and PTB, one between sarcoidosis and controls, and 22 between PTB and controls. The top five upregulated miRNAs (miR-132, miR-362-5p, miR-181c, miR-181a, and miR-512-3p) and two downregulated miRNAs (miR-454 and miR-139-5p) in sarcoidosis compared to PTB were selected for validation. Validation showed significant downregulation (p value <0.05) of only miR-454 in EBC of sarcoidosis patients compared to PTB patients with an optimal AUC of 0.663. miR-150* discriminated sarcoidosis patients from healthy controls with an AUC of 0.982. When PTB were compared to healthy controls, miR-454 and miR-139-5p were discriminating both groups with AUCs of 0.991 and 0.994 respectively in EBC. Conclusions: These findings suggest that while miR-454 differentiated pulmonary sarcoidosis from pulmonary tuberculosis, their clinical utility in EBC is limited. Further investigation is needed to explore their diagnostic potential, and to improve diagnostic accuracy in EBC.